Laparoscopic management of short-interval interstitial pregnancy after recent tubal ectopic pregnancy: A case report - Megan Bernstein; Michelle Han (Elsevier, 2024)
A 24-year-old woman, G6P2032, initially presented with a right-sided ruptured tubal ectopic pregnancy. Salpingectomy was performed with care to completely remove the fallopian tube. The patient then presented with ipsilateral interstitial pregnancy 11 weeks later and initially underwent systemic methotrexate injection, which failed to resolve the pregnancy. She then underwent laparoscopic cornuostomy and dilation and curettage. Cornuostomy was performed with injection of dilute vasopressin around the gestational sac to help minimize blood loss, followed by hydrodissection and sharp dissection to remove the pregnancy. Judicial electrocautery was used and the myometrium and serosa were closed in layers. Attention was given to preserve uterine myometrial tissue integrity at the cornua.The patient recovered and was discharged. Her beta-hCG level trended from 11,902 mIU/mL pre-surgery to 7726 on postoperative day 0, and 289 on postoperative day 7. Pathology from the interstitial region showed fragments of chorionic villi, and the dilation and curettage pathology demonstrated decidualized secretory endometrium.Short-interval interstitial ectopic pregnancies after prior salpingectomy for tubal ectopic pregnancy are extremely rare. This case demonstrated successful management with a minimally invasive laparoscopic cornuostomy. This case also displays that ipsilateral interstitial pregnancy can occur after salpingectomy even after care is taken to remove all visible portions of the fallopian tube. Thus, patients should be counseled carefully about the risks of short-interval pregnancy after a recent tubal ectopic pregnancy.